The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00294-022-01229-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophage-encoded gene VpaChn25_0734 amplifies ecological persistence of Vibrio parahaemolyticus CHN25

Abstract: Vibrio parahaemolyticus is a waterborne pathogen that can cause acute gastroenteritis, wound infection, and septicemia in humans. The molecular basis of its pathogenicity is not yet fully understood. Phages are found most abundantly in aquatic environments and play a critical role in horizontal gene transfer. Nevertheless, current literature on biological roles of prophage-encoded genes remaining in V. parahaemolyticus is rare. In this study, we characterized one such gene VpaChn25_0734 (543-bp) in V. parahaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Approximately 16 DEGs involved in PTS, arginine biosynthesis, and carotenoid biosynthesis were downregulated at the transcription level (0.014-to 0.430-fold, p < 0.05) in S. aureus ATCC8095 (Table S1). For example, the PTS plays a very important role in carbohydrate transport and controls a variety of cellular process [18,19]. Remarkably, in this study, the expression of seven DEGs encoding sugar, mannose, galactitol, and ascorbate transporter subunits were significantly inhibited (0.021-to 0.430-fold, p < 0.05), suggesting inactive transport of these carbohydrates induced by GMPE treatment.…”
Section: The Major Changed Metabolic Pathways In S Aureus Atcc8095mentioning
confidence: 51%
“…Approximately 16 DEGs involved in PTS, arginine biosynthesis, and carotenoid biosynthesis were downregulated at the transcription level (0.014-to 0.430-fold, p < 0.05) in S. aureus ATCC8095 (Table S1). For example, the PTS plays a very important role in carbohydrate transport and controls a variety of cellular process [18,19]. Remarkably, in this study, the expression of seven DEGs encoding sugar, mannose, galactitol, and ascorbate transporter subunits were significantly inhibited (0.021-to 0.430-fold, p < 0.05), suggesting inactive transport of these carbohydrates induced by GMPE treatment.…”
Section: The Major Changed Metabolic Pathways In S Aureus Atcc8095mentioning
confidence: 51%
“…This could reflect their fastidious nature, but the success of the two northernmost Atlantic populations harboring inoviruses contrasting with the unsuccessful lineages that lacked them signals alternatives are possible: that inoviruses may confer advantages in some as yet undefined context. For example, shed inovirus virions contribute to biofilm matrix ( 65 ) thereby promoting virulence and antimicrobial resistance but also potentially enhancing survival during long-distance movement on particles ( 53 , 55 , 66 68 ). Shed inoviruses can mislead human immune responses and decrease host ability to clear bacterial infections, thereby enhancing virulence ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding major and minor capsid proteins, tail protein, head and tail connector protein, small and large subunits of the terminase were found to be upregulated in the biofilm. Previous RNA-seq studies have revealed that Vibrio parahaemolyticus , after the removal of prophage, exhibited a reduced ability to form biofilms due to a change in the cell surface hydrophobicity ( Xu et al, 2022 ). However, few studies have been conducted on prophage induction within the biofilm context.…”
Section: Resultsmentioning
confidence: 99%